2009
DOI: 10.1029/2008rs004017
|View full text |Cite
|
Sign up to set email alerts
|

Vertical air motion in midlevel shallow‐layer clouds observed by 47‐MHz wind profiler and 532‐nm Mie lidar: Initial results

Abstract: [1] Variations of vertical air velocity (W) in the midlevel shallow-layer clouds are described by a case study observed at West Sumatra, Indonesia (0.2°S, 100.32°E), in the nighttime between 8 and 9 May 2004. By receiving echoes from refractive index irregularities, W and spectral width (s W ), used as a proxy of W turbulence, were observed both in clear and cloud regions using frequency power spectrum obtained by a 47-MHz wind profiler with 150-m vertical and 166-s time resolutions. Using altitude profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…It is mainly sensitive to temperature and humidity irregularities at the Bragg scale (i.e., half the radar wavelength, ∼3 m) in both cloudy and clear air conditions. Therefore, vertical air motions can also be measured in cloudy conditions [e.g., Yamamoto et al ., 2009]. MUR was operated for about one month in October‐November 2008 in a range imaging mode using frequency diversity and the adaptive Capon method in order to estimate vertical profiles of echo power (in arbitrary units) at a vertical resolution much better than 150 m [e.g., Luce et al , 2006].…”
Section: Radar Set‐upmentioning
confidence: 99%
“…It is mainly sensitive to temperature and humidity irregularities at the Bragg scale (i.e., half the radar wavelength, ∼3 m) in both cloudy and clear air conditions. Therefore, vertical air motions can also be measured in cloudy conditions [e.g., Yamamoto et al ., 2009]. MUR was operated for about one month in October‐November 2008 in a range imaging mode using frequency diversity and the adaptive Capon method in order to estimate vertical profiles of echo power (in arbitrary units) at a vertical resolution much better than 150 m [e.g., Luce et al , 2006].…”
Section: Radar Set‐upmentioning
confidence: 99%
“…Further, in the top part of clouds (0-500 m below the cloud tops), downward wind up to 0.2-0.3 m s -1 , which was caused by radiative cooling, was observed. For further discussion on the generation mechanism of turbulence, see Yamamoto et al (2009a). From a case study using data measured by the MU radar and Raman/Mie lidar, Yamamoto et al (2009b) showed a clear relation between the cloud-top altitude of mid-latitude cirrus and the bottom altitude of subtropical jet with high time and altitude resolutions (12 min and 150 m, respectively).…”
Section: Particle Fall Velocitymentioning
confidence: 99%
“…9. Time-altitude plots of (a) backscattered power measured by a 532-nm Mie lidar, and (b) vertical wind velocity and (c) spectral width measured by the vertical beam of the EAR (Yamamoto et al, 2009a). Thick black curves in each panel indicate cloud boundaries estimated by the lidar backscattered power.…”
Section: Particle Fall Velocitymentioning
confidence: 99%
“…Vertical wind (w) in Figure 1(b), an indicator of mountain-wave activity, is mostly calm, with small-amplitude background gravity waves, except for some increased variance associated with the turbulent layer. Yamamoto et al (2009) show time series of w measured in similar turbulent layers.…”
Section: -3 July 1998mentioning
confidence: 99%
“…Rao et al (2001) and Nastrom and Eaton (2005) measured average turbulence levels using MST radar; this study looks at distinct layers of turbulence stronger than the background level with spectral width over ∼1 m s − 1 (comparable to breaking mountain waves (Worthington, 1998)). Yamamoto et al (2009) showed one MST radar case study of a turbulent cloud layer at 6.0-8.5 km height. Gultepe and Starr (1995) and Smith and Jonas (1996) observed turbulence from convection and/or KHI in cirrus clouds.…”
Section: Introductionmentioning
confidence: 99%